Distant metastases in colorectal carcinoma: A proposal for a new M1 subclassification. Issue 9 (September 2016) - Merkel, S.; Weber, K.; Croner, R.S.; Golcher, H.; Göhl, J.; Agaimy, A.; Semrau, S.; Siebler, J.; Wein, A.; Hohenberger, W.; Wittekind, C.
Abstract: Introduction: In 2010, the seventh Tumour-Node-Metastasis (TNM) cancer staging system of the International Union for Cancer Control (UICC) and the American Joint Committee of Cancer (AJCC) introduced a subdivision of M1 in the TNM classification of colorectal carcinomas. For the eighth TNM edition which will be released in the autumn of 2016 and will become effective in January 2017 new proposals are appreciated. The aim of our study was to define a new and better proposal for M1 subclassification. Methods: In a total of 814 patients with stage IV colorectal carcinoma treated between 1995 and 2013 prognostic factors were analysed in univariate and multivariate analyses. Results: Advanced age, treatment in the earlier period 1995–2003, involvement of multiple metastatic sites, and non-curative resection were found to be independent prognostic factors. In patients with only one metastatic site, survival was good in patients with liver or lung metastasis, moderate in patients with metastasis of the peritoneum or non-regional lymph nodes and poor in patients with other rarely metastatic involved organs. The new proposal defines M1a, Metastasis confined to one organ: liver or lung (2-year survival 51.6%); M1b, Metastasis confined to one organ: peritoneum or non-regional lymph nodes, or Metastasis confined to liver plus lung (2-year survival 39.4%); and M1c, Metastasis confined to one organ: all other sites, or Metastasis in more than one organ, except liver plus lung (2-year survival 21.6%). Conclusion: The new proposal can identify three prognostic groups in stage IV colorectal carcinomas with significant differences in survival.